Transportation of heat generation/absorption and radiative heat flux in homogeneous–heterogeneous catalytic reactions of non-Newtonian fluid (Oldroyd-B model). (June 2020) - Wang, Jing; Ijaz Khan, M.; Khan, W.A.; Abbas, S.Z.; Imran Khan, M.
Highlights: Here three-dimensional flow of Oldroyd-B is addressed over a stretched surface. Stagnation point is considered. Electrically conducting fluid is considered. Ohmic heating and radiative heat flux are used in the mathematical modeling of energy equation. Abstract: Background: This study addresses the three-dimensional (3D) stagnation point flow of non-Newtonian material (Oldroyd-B) with magnetohydrodynamics. Furthermore, Ohmic heating and radiative flux are used in the modeling of energy expression. The surface is convectively heated. Equal strengths of diffusions for homogeneous and heterogeneous reactions are counted. Results are computed and presented graphically. Heat transfer rate is numerically discussed through table. Method: Here the nonlinear differential system first converted into ordinary differential equation through implementation of appropriate similarity variables. The obtained ordinary system is tackled through homotopy technique for convergent solutions. The outcomes are presented through different graphs and discussed in section six. Outcomes: The remarkable results of the present communication which is obtained from the semi analytical method i.e., "homotopy method" is summarized as (i) Opposite impact is noticed for velocity components i.e., ( f ′(ξ), g (ξ)) for rising fluid parameter and rotation parameter. (ii) The temperature is direct relation with Biot number and radiative variable. (iii) Heat transfer rate is more versus Biot number and radiation variable. (iv) The concentration field shows opposite impact versus homogeneous and heterogeneous parameters.